Intestinal failure following necrotizing enterocolitis: A clinical approach. (June 2016) - Jones, Kelsey D.J.; Howarth, Lucy J.
Abstract: Intestinal failure is a recognized complication of surgically-managed necrotizing enterocolitis (NEC). Functional adaptation of remaining bowel means that many children are eventually able to achieve enteral autonomy. Integrated multidisciplinary care in the early post-operative phase is key to long-term success. The objective of this review is to outline a clinical approach to management of intestinal and nutritional complications experienced by children following intestinal resection for NEC.